2019
DOI: 10.1590/0102-7786343051
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da Relação entre a Variabilidade dos índices de Vegetação e Temperatura da Região Nordeste do Brasil

Abstract: Resumo Esse estudo teve por objetivo investigar a inter-relação entre a variabilidade de índices de vegetação (NDVI - índice de Vegetação de Diferença Normalizada, VCI - índice de condição da vegetação) e temperatura (TCI - índice de Condição de Temperatura) sobre o Nordeste do Brasil, utilizando dados de sensoriamento remoto, banco de dados NOAA-NESDIS, obtidos na série histórica de 1982 a 2011. Foram feitas algumas inferências acerca da variação desses índices de vegetação e temperatura, associada as mudança… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…The results indicated that the VCI showed a better correlation with meteorological variables, between moderately and strongly positive, when compared to data of vegetation indexes (Table 5). This correlation has been corroborated in several international studies such as those of Zambrano et al (2016) and Gomes et al (2019), that demonstrated the VCI has a strong correlation with meteorological data, being considered a very useful tool for analysis in regions where there is a worsening drought. According to Xu et al (2020) and Gu et al (2019), the normalization of NDVI data in the VCI calculation process contributes to a moderate and strong correlation when compared with meteorological data.…”
Section: Comparative Analysis Of Ndvi Evi and Vci Indexes For Drought Monitoring In Watershed Regionsmentioning
confidence: 54%
See 1 more Smart Citation
“…The results indicated that the VCI showed a better correlation with meteorological variables, between moderately and strongly positive, when compared to data of vegetation indexes (Table 5). This correlation has been corroborated in several international studies such as those of Zambrano et al (2016) and Gomes et al (2019), that demonstrated the VCI has a strong correlation with meteorological data, being considered a very useful tool for analysis in regions where there is a worsening drought. According to Xu et al (2020) and Gu et al (2019), the normalization of NDVI data in the VCI calculation process contributes to a moderate and strong correlation when compared with meteorological data.…”
Section: Comparative Analysis Of Ndvi Evi and Vci Indexes For Drought Monitoring In Watershed Regionsmentioning
confidence: 54%
“…In studies related to drought, the vegetation indexes are applied to monitor the event through the Vegetation Condition Index (VCI), created by Kogan (1995), and applied using MODIS sensor data in event analysis of drought in biological reserves (BRANCO, 2016), as well as in comparison between drought delimitation indexes (JIAO et al, 2019;ZHANG et al, 2017). In addition, this technique is applied with the use of other remote sensing data, such as NOAA-NESDIS, in analyzes of vegetation tendency to drought variation (XU et al, 2020) and variability of vegetation and temperature indexes in Brazilian regions (GOMES et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…VCP registered 596 heatwaves in the period, while IAC registered only 346 heatwave days, with 230 coincident days. Such a difference was also observed in works that show intra-urban thermal variability, and it is explained, for example, by the different levels of urbanization in different regions (Rosenthal et al, 2014;Gomes et al, 2019;Lapola et al, 2019). Analogously, IAC weather station is located in an area with higher vegetation cover and population density of 1187,20 inhabitants per km 2 (Campinas, 2010), while VCP station is in a region with a higher level of urbanization (Fig.…”
Section: Comparing Iac and Vcp Heatwave Patternsmentioning
confidence: 57%
“…1a e 1b), isto é, quando no "verão" e "outono" ocorreram período de anos com o NDVI assumindo valores acima de 1,0, para o "inverno" e "primavera" essas valores decresceram, indicando menos atividade de fotosssintese pela cobertura vegetal, o que é consistente com estações mais secas nessas regiões do NEB. Pois o NDVI é controlado pela umidade, vários fatores causam alterações na leitura da vegetação segundo Gomes et al (2019), promovendo ruídos que possam resultar em incertezas associadas aos registros de NDVI e sua suscetibilidade e sensibilidade dos efeitos atmosféricos. Santos e Negri (1996) também relataram que o NDVI possui uma relação linear mais evidente com a precipitação, quando avaliamos regiões, cuja precipitação não ultrapassa 50 mm/mês, como algumas áreas das regiões semiáridas do NEB.…”
Section: Resultados E Discussõesunclassified